2019
DOI: 10.1002/jbmr.3677
|View full text |Cite
|
Sign up to set email alerts
|

Sirt1 Promotes Osteogenic Differentiation and Increases Alveolar Bone Mass via Bmi1 Activation in Mice

Abstract: Sirtuin 1 (Sirt1), a protein deacetylase, is a novel target for bone metabolism. To investigate whether overexpression of Sirt1 in mandibular mesenchymal stem cells (M-MSCs) increased alveolar bone mass in vivo, we generated Sirt1 transgenic mice (Sirt1 TG ), with Sirt1 gene expression driven by the Prx1 gene, which represents the mesenchymal lineage. Our results demonstrated that overexpression of Sirt1 in M-MSCs increased the alveolar bone volume in 1-month-old, 9-month-old, and 18-month-old Sirt1 TG mice co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 50 publications
1
50
0
Order By: Relevance
“…Other factors were also involved in the process of SIRT1 regulation of MSC, such as the activation of the adenosine monophosphate-activated protein kinase (AMPK)-SIRT1 signaling pathway as well as beneficial mechanical stretch to induce antioxidant responses, attenuate intracellular reactive oxygen species (ROS), and improve osteogenesis of human BM-MSCs [52]. In mice, Sirt1 promotes MSC proliferation and osteogenic differentiation and inhibits MSC senescence via Bmi1 activation; therefore, treatment with resveratrol could promote bone formation and prevent bone loss [53]. SIRT1 was also directly involved in the regulation of beige adipocyte differentiation.…”
Section: Effect Of Sirt 1 In Oamentioning
confidence: 99%
“…Other factors were also involved in the process of SIRT1 regulation of MSC, such as the activation of the adenosine monophosphate-activated protein kinase (AMPK)-SIRT1 signaling pathway as well as beneficial mechanical stretch to induce antioxidant responses, attenuate intracellular reactive oxygen species (ROS), and improve osteogenesis of human BM-MSCs [52]. In mice, Sirt1 promotes MSC proliferation and osteogenic differentiation and inhibits MSC senescence via Bmi1 activation; therefore, treatment with resveratrol could promote bone formation and prevent bone loss [53]. SIRT1 was also directly involved in the regulation of beige adipocyte differentiation.…”
Section: Effect Of Sirt 1 In Oamentioning
confidence: 99%
“…For in vitro generation and origination, the stemness of MSCs can be maintained in the early and middle generations of in vitro growth. However, stemness can experience a significant reduction once a critical time is exceeded [36,37]. Meanwhile, stem cells from different tissue sources have significant differences in their abilities to maintain stemness during in vitro culture.…”
Section: Discussionmentioning
confidence: 99%
“…Qu et al (43) revealed that SIRT1 was involved in osteogenic proliferation and differentiation by regulating miR-132-3p. Furthermore, Wang et al (44) demonstrated that SIRT1 promotes osteogenic differentiation and increases alveolar bone mass via B cell-specific Moloney murine leukemia virus integration site 1. in the present study, the expression of SIRT1 and its downstream target PGc-1α was discovered to be decreased in osteoblasts exposed to Dex. Therefore, it was speculated that the SIRT1/PGC-1α signaling pathway played an important role in the protective effects of NMN in Dex-treated BMSCs.…”
Section: Discussionmentioning
confidence: 99%